A concrete test specimen for erosion resistance testing
Patent Information
- Application Number
- CN202410007903.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-09
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2041-12-09
AI Technical Summary
但是只能做一个大致深浅的判断,无法实现精确的侵蚀深度的检测
[0042] In summary, this invention features a simple structure, convenient operation, higher reliability, and higher detection accuracy, enabling it to better detect the degree of sulfate erosion on concrete.
Smart Images

Figure CN117664843B_ABST
Abstract
Description
[0001] This application is a divisional application of the patent application No. 202111496130.5, filed on December 9, 2021, entitled "A Concrete Erosion Resistance Testing Device". Technical Field
[0002] This invention relates to the field of concrete structure erosion research technology, and specifically to a concrete specimen for erosion resistance testing. Background Technology
[0003] Concrete is the most common structural material in construction engineering, and research on the durability of concrete structures plays a crucial role in predicting their lifespan. Concrete structures in environments such as seawater, saline-alkali land, and acid rain are susceptible to sulfate erosion, leading to structural damage and reduced strength. Sulfate erosion is a significant mode of corrosion affecting concrete structures. In sulfate-rich environments, when concrete is eroded or subjected to pressure changes that cause cracks, sulfate penetrates the concrete through these cracks. Within the cracks, sulfate reacts with calcium hydroxide and hydrated calcium aluminate in the cement to form ettringite crystals, which expand to approximately 100% in volume. This ettringite crystal formation further widens and grows the cracks, allowing sulfate to penetrate even deeper, creating a vicious cycle that rapidly reduces the strength of the concrete structure. Therefore, studying the effects of sulfate erosion on concrete structures is of great significance and value in the field of concrete application research.
[0004] Existing experimental methods for studying sulfate erosion of concrete structures typically involve placing concrete specimens in a closed chamber within a sulfate environment, allowing them to erode for a period of time, and then assessing the extent of erosion through observation and strength testing. However, specimens are usually unable to be tested further after strength testing, necessitating multiple sets of specimens for comparison, which is costly and cumbersome. Therefore, directly obtaining the changes in sulfate erosion depth and intensity would provide a better assessment of the degree of erosion in concrete specimens.
[0005] CN201410681700.1 discloses a method for predicting the sulfate attack depth of concrete. This method includes: establishing a multi-parameter mathematical model for sulfate attack depth based on the diffusion coefficient of the concrete structure, the sulfate concentration on the concrete surface, the initial sulfate concentration inside the concrete, the stoichiometric coefficient, the content of calcium aluminate in the concrete structure, and combining time parameters and the decay index of the diffusion coefficient; obtaining a mathematical model for the attack depth at the time to be predicted based on the first and second time moments and their corresponding attack depths; and obtaining the attack depth at the time to be predicted based on the mathematical model for the attack depth at the time to be predicted. This method, through the established sulfate attack depth prediction model, can predict the attack depth in practical engineering applications without needing to obtain specific values of parameters such as the concentration, temperature, and attack mode of the sulfate solution in the environment, as well as the tricalcium aluminate content in the cement. However, this method relies purely on simulation and theoretical calculations to obtain the attack depth, resulting in poor reliability and practicality.
[0006] CN202110648138.2 previously disclosed a method for detecting the depth of chloride ion erosion in concrete. First, a silver nitrate solution is sprayed onto the cross-section of the concrete. In areas containing chloride ions, the chloride ions combine with silver ions to form silver chloride precipitate; while in areas without chloride ion erosion, free silver ions are present. Then, a colorimetric solution for detecting silver ions is sprayed. Areas containing chloride ions do not show color, while areas without chloride ions do. The depth of chloride ion erosion is determined by the color difference. This method is convenient, fast, and widely applicable. However, it can only provide a rough assessment of the depth and cannot achieve precise detection of erosion depth.
[0007] CN202110629087.9 disclosed a method and system for detecting the sound velocity of ultrasonic waves to test the performance of concrete. The method uses ultrasonic detection to obtain the erosion depth, but it still has the drawbacks of high cost and low practicality.
[0008] Therefore, in order to better detect the depth of sulfate attack, the inventors considered converting the expansion force of sulfate crystallization at the crack tip of concrete specimens into forward pressure, and obtaining the sulfate attack depth by detecting this pressure. This would allow for a better assessment of the concrete structure's resistance to sulfate attack. However, designing a device that can implement this detection method, while being simple in structure, easy to operate, and capable of effectively controlling the pressure to accelerate the testing rate, remains a problem that requires further consideration and resolution. Summary of the Invention
[0009] To address the shortcomings of the existing technology, the technical problem this invention aims to solve is: how to provide a concrete corrosion resistance testing device with a simple structure, convenient pressure adjustment to accelerate the testing rate, and the ability to easily detect the pressure generated by sulfate reaction crystallization at the tip of concrete cracks to obtain the crack erosion depth. This invention also provides a concrete specimen for corrosion resistance testing that can easily and conveniently obtain crack depth and growth time to determine the degree of sulfate erosion.
[0010] To solve the above-mentioned technical problems, the present invention adopts the following technical solution: A concrete corrosion resistance testing device is characterized by comprising a test chamber containing a test chamber in which a concrete specimen is placed. A sealed door for taking out and placing the concrete specimen is also provided on the side wall of the test chamber. A pressure chamber is also provided in the test chamber at an interval from the test chamber. A sealed elastic partition is provided between the pressure chamber and the test chamber. An air inlet pipe is connected to the pressure chamber and an air pump is installed on it.
[0011] In this way, the test chamber is used to create a test fluid environment rich in sulfate components. After the concrete specimen is placed inside, air is introduced into the pressurized chamber through an air pump. Then, the pressure inside the test chamber is uniformly and stably compressed through an elastic partition, allowing cracks generated on the concrete specimen to grow rapidly, thus achieving the sulfate erosion test. Therefore, the test progress can be accelerated more stably, uniformly, and quickly to obtain the erosion resistance of the concrete specimen.
[0012] Furthermore, a pressure detection sensor is also installed in the test chamber. The pressure detection sensor is connected to the control device, and the control device is connected to the air intake pump.
[0013] This allows for the detection of pressure within the test chamber and feedback control of the air intake pump, ensuring a stable test pressure within the test chamber to accelerate the test.
[0014] Furthermore, a sulfate solution spraying device is also installed in the test chamber.
[0015] This allows for the convenient and quick creation of a high-concentration sulfate fog environment within the test chamber, facilitating corrosion testing.
[0016] Furthermore, a sulfate concentration probe is also installed in the test chamber. The sulfate concentration probe is connected to a control device, and the control device is connected to a sulfate solution spraying device.
[0017] This allows for precise adjustment and maintenance of the sulfate concentration within the test chamber through detection feedback control.
[0018] Furthermore, the test chamber is also equipped with specimen support platforms spaced apart on the left and right, and a pressure device is installed above the middle space of the specimen support platforms.
[0019] This allows concrete specimens to be placed on a specimen support platform and then pressure applied by a pressure device to induce cracks or accelerate crack growth, thus facilitating faster testing.
[0020] Furthermore, the concrete specimen is made from the concrete to be tested, and multiple sets of strain gauges are embedded inside the concrete specimen at different depths from the test surface. The strain gauges are connected to the concrete specimen and the control device through connecting wires embedded in the concrete specimen.
[0021] This concrete specimen is used for concrete corrosion resistance testing. Typically, cracks are first generated on the test surface of the concrete specimen (this can be achieved by applying a load). The specimen is then placed in a test fluid environment rich in sulfates (i.e., the test chamber). Pressure can be applied to the fluid around the specimen and / or a continuous load can be applied to the specimen itself, allowing the cracks to grow. During crack growth, a small reaction pool forms at the crack tip. Sulfates react with calcium hydroxide and hydrated calcium aluminate within the concrete in this pool, producing ettringite crystals that expand, further widening the crack and extending it inwards. This cycle continues, gradually deepening the crack. Therefore, when the crack reaches the strain gauge location, the expanded ettringite crystals exert pressure on the strain gauge. The strain gauge senses this pressure signal, allowing the determination of the crack depth and time. The size of the crack can also be determined based on the pressure, thus indicating the corrosion resistance of the concrete specimen. Therefore, this method provides a simple and convenient way to obtain crack depth and growth time to assess the degree of sulfate corrosion.
[0022] Furthermore, a connector is provided at the end of the connecting line that connects to the outside of the concrete specimen.
[0023] This makes it easy to connect to the control device via the connector.
[0024] Furthermore, the strain gauges are set parallel to the testing surface of the concrete specimen.
[0025] This allows for better detection of the positive pressure generated by the expansion of crystal growth at the crack tip.
[0026] Furthermore, the concrete specimen is a horizontally arranged rectangular column with four sides along its length serving as testing surfaces. Each set of strain gauges is arranged in a proportionally sized rectangle along the cross-section of the concrete specimen.
[0027] This not only makes it easier to apply pressure to the concrete specimens, but also allows for better testing by setting strain gauges on multiple test surfaces.
[0028] Furthermore, the strain gauge is mounted and fixed on the inner side of a rectangular frame structure made of rigid material.
[0029] This facilitates the installation and protection of strain gauges, and the support frame can easily bear the force when the strain gauges are subjected to stress, enabling the detection to be performed.
[0030] Furthermore, the support frame is coaxial and spaced apart with multiple strain gauges of different sizes, and each set of strain gauges is installed on the support frame of different sizes.
[0031] This makes it easier for each group of strain gauges to detect at different depths.
[0032] Furthermore, a strain gauge mounting groove is provided on the outer surface of the support frame. The depth of the strain gauge mounting groove is the same as the thickness of the strain gauge, and the strain gauge is installed in the mounting groove.
[0033] This facilitates better installation and protection of the strain gauges. During implementation, wiring channels are also provided on the outer surface of the support frame for arranging connecting wires.
[0034] Furthermore, a mesh skeleton is provided on the outer surface of the strain gauge, and the mesh size of the mesh skeleton is smaller than the minimum aggregate size of the concrete specimen.
[0035] In this way, the mesh skeleton can protect the strain gauge during the production of concrete specimens, preventing it from being damaged by aggregates and concrete. More importantly, during specimen testing, when the crack tip reaches the strain gauge, it first contacts and acts on the mesh skeleton. Because the mesh skeleton is a rigid material, it can effectively shield the lateral expansion force generated during crack formation, preventing this expansion force from affecting the strain gauge. This allows the strain gauge to only bear the forward positive pressure generated by the crystallization expansion at the crack tip, enabling better test detection. At the same time, because the crack tip is constrained by the mesh skeleton due to lateral expansion, the forward pressure of crystallization expansion is greater, thus significantly improving the sensitivity of the strain gauge detection.
[0036] Furthermore, the mesh framework is made of steel wire mesh.
[0037] This gives it sufficient hardness to better achieve the aforementioned effects.
[0038] Furthermore, the mesh skeleton has a rectangular frame structure and is fitted over the supporting frame.
[0039] This makes installation and fixation easier and improves the protective effect.
[0040] Furthermore, an elastic material isolation membrane is also attached to the outer surface of the strain gauge.
[0041] In this way, the isolation membrane not only better protects the strain gauge from concrete erosion during specimen production, but more importantly, its presence ensures that the crack tip can only extend to the isolation membrane. The membrane's elasticity allows some of the expansion force acting on the strain gauge through the mesh skeleton to be transferred to the isolation membrane and neutralized by its elasticity as the crack expands. This further prevents the force of the crack extending laterally from affecting the strain gauge, ensuring that the strain gauge only bears the forward expansion force for better detection. Simultaneously, the membrane's elasticity allows it to open slightly when the crack tip reaches the strain gauge, allowing the crystallization expansion effect within the crack to act forward on the strain gauge, preventing the crack from completely failing to open and thus rendering the strain gauge unable to bear force. During implementation, the isolation membrane is positioned between the mesh skeleton and the strain gauge. As can be seen from the above principle, the simultaneous presence of the isolation membrane and the mesh skeleton not only better prevents the expansion force of the crack from acting on the strain gauge, but also complements each other, better protecting the strain gauge and improving its detection effect. During implementation, the isolation membrane is sealed and fixed to the support frame on all sides, while the isolation membrane and strain gauge can slide freely between them. To ensure that the above-mentioned effects of the separator can be better achieved.
[0042] In summary, this invention features a simple structure, convenient operation, higher reliability, and higher detection accuracy, enabling it to better detect the degree of sulfate erosion on concrete. Attached Figure Description
[0043] Figure 1 This is a schematic diagram of the concrete erosion resistance testing device according to a specific embodiment of the present invention.
[0044] Figure 2 for Figure 1 A schematic diagram of the concrete specimen to be tested.
[0045] Figure 3 for Figure 2 Cross-sectional view.
[0046] Figure 4 for Figure 3 A magnified structural diagram of the individual strain gauge located at the center circle position. Detailed Implementation
[0047] The present invention will now be described in further detail with reference to specific embodiments. Detailed implementation method:
[0049] See Figure 1-4A concrete corrosion resistance testing device is characterized by comprising a test chamber 6, which has a test chamber 7, in which a concrete specimen 1 is placed. A sealed door 9 for taking out and placing the concrete specimen is also provided on the side wall of the test chamber. A pressure chamber 8 is also provided in the test chamber at an interval from the test chamber. A sealed elastic partition 10 is provided between the pressure chamber and the test chamber. An air inlet pipe 12 is connected to the pressure chamber and an air pump 11 is installed on it.
[0050] In this way, the test chamber is used to create a test fluid environment rich in sulfate components. After the concrete specimen is placed inside, air is introduced into the pressurized chamber through an air pump. Then, the pressure inside the test chamber is uniformly and stably compressed through an elastic partition, allowing cracks generated on the concrete specimen to grow rapidly, thus achieving the sulfate erosion test. Therefore, the test progress can be accelerated more stably, uniformly, and quickly to obtain the erosion resistance of the concrete specimen.
[0051] The test chamber is also equipped with a pressure detection sensor 13, which is connected to the control device 4, and the control device is connected to the air intake pump 11.
[0052] This allows for the detection of pressure within the test chamber and feedback control of the air intake pump, ensuring a stable test pressure within the test chamber to accelerate the test.
[0053] The test chamber 7 is also equipped with a sulfate solution spraying device 14.
[0054] This allows for the convenient and quick creation of a high-concentration sulfate fog environment within the test chamber, facilitating corrosion testing. In practice, the sulfate solution spraying device 14 can be externally connected to a sulfate solution spraying pipeline and a spray pump, and is also connected to a sulfate solution raw material tank (not shown in the figure).
[0055] The test chamber is also equipped with a sulfate concentration probe 15, which is connected to a control device 4, and the control device is connected to a sulfate solution spraying device 14.
[0056] This allows for precise adjustment and maintenance of the sulfate concentration within the test chamber through detection feedback control.
[0057] The test chamber is also equipped with specimen support platforms 16 spaced apart on the left and right, and a pressure device 17 is installed above the middle space of the specimen support platforms 16.
[0058] This allows concrete specimens to be placed on a specimen support platform and then pressure applied by a pressure device to induce cracks or accelerate crack growth, thus facilitating faster testing.
[0059] The concrete specimen 1 is made from the concrete to be tested. Multiple strain gauges 2 are embedded inside the concrete specimen at different depths from the test surface. The strain gauges 2 are connected to the concrete specimen 1 and the control device 4 through the connecting wires 3 embedded in the concrete specimen.
[0060] This concrete specimen is used for concrete corrosion resistance testing. Typically, cracks are first generated on the test surface of the concrete specimen (this can be achieved by applying a load). The specimen is then placed in a test fluid environment rich in sulfates (i.e., the test chamber). Pressure can be applied to the fluid around the specimen and / or a continuous load can be applied to the specimen itself, allowing the cracks to grow. During crack growth, a small reaction pool forms at the crack tip. Sulfates react with calcium hydroxide and hydrated calcium aluminate within the concrete in this pool, producing ettringite crystals that expand, further widening the crack and extending it inwards. This cycle continues, gradually deepening the crack. Therefore, when the crack reaches the strain gauge location, the expanded ettringite crystals exert pressure on the strain gauge. The strain gauge senses this pressure signal, allowing the determination of the crack depth and time. The size of the crack can also be determined based on the pressure, thus indicating the corrosion resistance of the concrete specimen. Therefore, this method provides a simple and convenient way to obtain crack depth and growth time to assess the degree of sulfate corrosion. In practice, the control device is a computer-enabled control device, which is existing technology and will not be described in detail here.
[0061] A connector 5 is provided at the end of the connecting line that connects to the outside of the concrete specimen 1.
[0062] This makes it easy to connect to the control device via the connector.
[0063] Among them, strain gauge 2 is set parallel to the detection surface of concrete specimen 1.
[0064] This allows for better detection of the positive pressure generated by the expansion of crystal growth at the crack tip.
[0065] The concrete specimen 1 is a horizontally arranged rectangular column with four sides along its length serving as testing surfaces. Each set of strain gauges 2 is arranged in a proportionally symmetrical rectangle along the cross-section of the concrete specimen.
[0066] This not only makes it easier to apply pressure to the concrete specimens, but also allows for better testing by setting strain gauges on multiple test surfaces.
[0067] The strain gauge 2 is mounted and fixed on the inner side of a rectangular frame structure made of rigid material, which is supported by a support frame 20.
[0068] This facilitates the installation and protection of strain gauges, and the support frame can easily bear the force when the strain gauges are subjected to stress, enabling the detection to be performed.
[0069] Among them, the support frame 20 is coaxial and has multiple supports of different sizes at intervals, and each set of strain gauges is installed on the support frame of different sizes.
[0070] This makes it easier for each group of strain gauges to detect at different depths.
[0071] Among them, the outer surface of the support frame 20 is provided with a strain gauge mounting groove 21, the depth of the strain gauge mounting groove 21 is the same as the thickness of the strain gauge 2, and the strain gauge 2 is installed in the mounting groove.
[0072] This facilitates better installation and protection of the strain gauges. During implementation, wiring channels are also provided on the outer surface of the support frame for arranging connecting wires.
[0073] Among them, the outer surface of the strain gauge 2 is also provided with a mesh skeleton 22, and the mesh size of the mesh skeleton 22 is smaller than the minimum aggregate size of the concrete specimen.
[0074] In this way, the mesh skeleton can protect the strain gauge during the production of concrete specimens, preventing it from being damaged by aggregates and concrete. More importantly, during specimen testing, when the crack tip reaches the strain gauge, it first contacts and acts on the mesh skeleton. Because the mesh skeleton is a rigid material, it can effectively shield the lateral expansion force generated during crack formation, preventing this expansion force from affecting the strain gauge. This allows the strain gauge to only bear the forward positive pressure generated by the crystallization expansion at the crack tip, enabling better test detection. At the same time, because the crack tip is constrained by the mesh skeleton due to lateral expansion, the forward pressure of crystallization expansion is greater, thus significantly improving the sensitivity of the strain gauge detection.
[0075] Among them, the mesh skeleton 22 is steel wire mesh.
[0076] This gives it sufficient hardness to better achieve the aforementioned effects.
[0077] The mesh skeleton 22 has a rectangular frame structure and is fitted outside the support frame 20.
[0078] This makes installation and fixation easier and improves the protective effect.
[0079] Among them, a layer of elastic material isolation membrane 23 is also attached to the outer surface of the strain gauge 2.
[0080] In this way, the isolation membrane not only better protects the strain gauge from concrete erosion during specimen production, but more importantly, its presence ensures that the crack 24 can only extend to the isolation membrane. The elasticity of the isolation membrane allows some of the expansion force acting on the strain gauge through the mesh skeleton to act on the isolation membrane and be offset by its elasticity when the crack expands. This further better avoids the impact of the crack's lateral expansion force on the strain gauge, allowing it to only bear the forward expansion force for better detection. Simultaneously, the elasticity of the isolation membrane allows it to open a certain gap when the crack reaches the strain gauge, allowing the expansion effect of the crystals 25 within the crack to act forward on the strain gauge, preventing the crack from completely failing to open and thus rendering the strain gauge unable to bear force. During implementation, the isolation membrane is positioned between the mesh skeleton and the strain gauge. As can be seen from the above principle, the simultaneous presence of the isolation membrane and the mesh skeleton not only better prevents the crack's lateral expansion force from acting on the strain gauge, but also complements each other, better protecting the strain gauge and improving its detection effect. During implementation, the isolation membrane is sealed and fixed to the support frame on all four sides, while the isolation membrane and strain gauges can slide freely between each other. This ensures that the aforementioned effects of the isolation membrane can be better achieved.
Claims
1. A concrete specimen for erosion resistance testing, said concrete specimen being made from the concrete to be tested, characterized in that, Multiple strain gauges are embedded inside the concrete specimen at different depths from the test surface of the concrete specimen. The strain gauges are connected to the concrete specimen and the control device through connecting wires embedded in the concrete specimen. The strain gauge is mounted and fixed on the inner side of a rectangular frame structure made of rigid material; The support frame is coaxial and has multiple strain gauges of different sizes spaced apart, and each set of strain gauges is installed on the support frame of different sizes. The outer surface of the support frame is provided with strain gauge mounting grooves. The depth of the strain gauge mounting grooves is the same as the thickness of the strain gauges, and the strain gauges are installed in the mounting grooves. The outer surface of the strain gauge is also provided with a mesh skeleton, the mesh size of which is smaller than the minimum aggregate size of the concrete specimen. The mesh skeleton is used to contact and act on the strain gauge when the crack tip reaches the strain gauge position, so as to shield the expansion force that is generated to both sides during the crack formation process, so that the strain gauge only bears the forward positive pressure generated by the crystallization expansion at the crack tip.
2. The concrete specimen for corrosion resistance testing as described in claim 1, characterized in that, A connector is provided at the end of the connecting wire that connects to the outside of the concrete specimen.
3. The concrete specimen for corrosion resistance testing as described in claim 1, characterized in that, The strain gauges are set parallel to the test surface of the concrete specimen.
4. The concrete specimen for corrosion resistance testing as described in claim 1, characterized in that, The concrete specimen is a horizontally arranged rectangular column with four sides along its length serving as testing surfaces. Each set of strain gauges is arranged in a proportionally equal rectangle along the cross-section of the concrete specimen.
5. The concrete specimen for corrosion resistance testing as described in claim 1, characterized in that, The mesh skeleton is made of steel wire mesh.
6. The concrete specimen for corrosion resistance testing as described in claim 1, characterized in that, The mesh skeleton has an overall rectangular frame structure and is fitted outside the supporting frame; A layer of elastic material is also attached to the outer surface of the strain gauge.
Citation Information
Patent Citations
A Method for Predicting the Depth of Concrete Sulfate Attack
CN104406904B
Ultrasonic sound velocity detection method and system for detecting performance of concrete
CN113390970A
Detection method for concrete chloride ion erosion depth
CN113607722A
Strain gauge mounted in a support , in particular for lifting machines
EP0969265A1
Stress monitoring sensor and stress monitoring method
JP2020056768A